DUCS 2.0: exploring new frontiers in research - Universiti Teknologi MARA, Research & Innovation Division (Research and Innovation Division, 2025)
This initiative by BPI, UiTM Selangor, aims to provide a platform for engagement and knowledge- sharing among researchers from various fields of expertise. The primary objectives are to foster research collaboration, strengthen grant proposal writing, and stimulate high-impact publications in targeted research areas. The publication of high-quality research outcomes through this effort is hoped to elevate the expertise and visibility of our researchers at both national and international levels.